PENDAMPINGAN SISWA KORBAN BROKEN HOME MELALUI PENERAPAN CBT (COGNITIVE BEHAVIOR THERAPY) UNTUK MENINGKATKAN KEDISIPLINAN DI MA AL-WATHAN LARANGAN PERRENG - Moh. Wardi; Heri Fadli Wahyudi; Musyfiquddin; Nazlah Hidayati (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This service aims to provide assistance through Cognitive Behavioral Therapy (CBT) for students who experience broken homes at MA Al-Wathan Larangan Perreng, where students with broken home family backgrounds are found to tend to experience discipline problems, such as indiscipline, skipping behavior, and other negative behaviors in the school environment. The methodology used is Asset Based on Community Development (ABCD) which is a form of analysis to determine the potential, find strengths, and assets that can be utilized to improve the discipline of students who experience broken homes. The results of the service show that CBT is effective in helping students identify and change negative thought patterns that affect their behavior. Through the CBT therapy process, students are better able to control their emotions, increase awareness of the consequences of their actions, and develop skills in solving problems more adaptively. In addition, support from counseling teachers and the school environment are important factors in the successful implementation of CBT.